Selective Dorsal Rhizotomy in Treatment of Spasticity in Patients with Cerebral Palsy - Olga A. Klochkova; Ekaterina P. Kolesnikova; Dmitriy Yu. Zinenko; Evgeniya M. Berdichevskaya (Вопросы современной педиатрии, 2022)
Selective dorsal rhizotomy (SDR) is effective and safe neurosurgical method for the treatment of patients with spastic forms of cerebral palsy (CP). The aim of the review is to introduce the opportunities of SDR in CP patients, to present indications, contraindications, and current inclusion criteria for the surgery for the broad audience of specialists. Authors have given recommendations on SDR implementation in complex rehabilitation of CP patients and have defined its effective combination with other methods of spasticity treatment according to the international experience of SDR, and its short-term and long-term results. The particular attention was paid to the application of SDR in cases of secondary orthopaedic deformities due to CP. The understanding of opportunities and limitations of SDR will allow us to give the patients relevant help and use the advantages of this method.